Project on Human Development in Chicago Neighborhoods (PHDCN): Flagged Instrument List, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. In the Flagged Instrument List, Wave 3 instruments were identified for which there may have been problems. These problems included such things as another person being present while the respondent was interviewed, the respondent not being totally honest, or the respondent not understanding. The list was compiled by interviewers for nearly every Wave 3 instrument administered. The following Wave 3 studies were not included: PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): MASTER FILE, WAVE 3, 2000-2002 (ICPSR 13668), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): ADDENDUM (PRIMARY CAREGIVER), WAVE 3, 2000-2002 (ICPSR 13670), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): ADDENDUM (YOUNG ADULT), WAVE 3, 2000-2002 (ICPSR 13671), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): CHILD AND ADOLESCENT BEHAVIOR RATING SCALE, WAVE 3, 2000-2002 (ICPSR 13678), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): COMMUNITY INVOLVEMENT AND COLLECTIVE EFFICACY (YOUNG ADULT), WAVE 3, 2000-2002 (ICPSR 13686), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): FAMILY LEGAL UPDATE (YOUNG ADULT), WAVE 3, 2000-2002 (ICPSR 13704), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): HEADER DATA (PRIMARY CAREGIVER), WAVE 3, 2000-2002 (ICPSR 13712), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): HEADER DATA (SUBJECT AND YOUNG ADULT), WAVE 3, 2000-2002 (ICPSR 13713), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): INTERVIEWER IMPRESSIONS (PRIMARY CAREGIVER), WAVE 3, 2000-2002 (ICPSR 13718), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): INTERVIEWER IMPRESSIONS (SUBJECT), WAVE 3, 2000-2002 (ICPSR 13719), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): INTERVIEWER IMPRESSIONS (YOUNG ADULT), WAVE 3, 2000-2002 (ICPSR 13720), PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): WECHSLER ADULT INTELLIGENCE SCALE-REVISED, WAVE 3, 2000-2002 (ICPSR 13747). No further information was provided to ICPSR regarding what, if anything, was done regarding flagged instruments.